Analisa Tidak Linier Mekanisme Keruntuhan Jembatan Busur Rangka Baja (A-Half Through Arch) - Abdul Rochim; Data Iranata; Bambang Piscesa; Navir Afif Refani (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2019)
The collapses of steel truss bridges can be caused by some factors such as vehicle overloads, material deterioration (corrosion, fatigue), and unexpected tsunami and/or earthquake loads. However, in this paper, the study is limited only to the failure of a-half through arch bridge due to earthquake loads. The bridge has a 100 m long span and is designed using the response spectrum of Surabaya city, East Java, Indonesia. Static nonlinear push-over analysis is used to investigate the performance and the collapse mechanism of the bridge. The bridge was designed based on SNI 1725-2016 and SNI 2833-2016. From the analysis, the failure of the structural elements occurred in the arch members located somewhere near the end portal. The performance level of the bridge determined using the Capacity Spectrum Method [1] is at the Immediate Occupancy (IO) level.